2021
DOI: 10.1186/s40035-021-00234-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive assays for detection of plasma tau and phosphorylated tau 181 in Alzheimer’s disease: a systematic review and meta-analysis

Abstract: A lack of convenient and reliable biomarkers for diagnosis and prognosis is a common challenge for neurodegenerative diseases such as Alzheimer’s disease (AD). Recent advancement in ultrasensitive protein assays has allowed the quantification of tau and phosphorylated tau proteins in peripheral plasma. Here we identified 66 eligible studies reporting quantification of plasma tau and phosphorylated tau 181 (ptau181) using four ultrasensitive methods. Meta-analysis of these studies confirmed that the AD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 107 publications
2
27
0
5
Order By: Relevance
“…In the present study, plasma t-tau levels were significantly higher in patients with probable AD than in healthy controls, similar to the findings of most published results (Mattsson et al, 2016 ; Lue et al, 2017 ), whereas several studies also found that plasma t-tau levels showed the opposite result or no significant difference between them (Sparks et al, 2012 ; Verberk et al, 2018 ; Qu et al, 2021 ). In a large meta-analysis, it was confirmed that patients with AD had higher plasma t-tau levels than controls, which may reflect neuronal damage as a nonspecific marker (Jack et al, 2018 ; Ding et al, 2021 ). Mattson et al found that the higher plasma t-tau level was associated with AD dementia and showed significant correlations with poor cognition, greater atrophy, and hypometabolism during follow-up in the AD Neuroimaging Initiative study (Mattsson et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, plasma t-tau levels were significantly higher in patients with probable AD than in healthy controls, similar to the findings of most published results (Mattsson et al, 2016 ; Lue et al, 2017 ), whereas several studies also found that plasma t-tau levels showed the opposite result or no significant difference between them (Sparks et al, 2012 ; Verberk et al, 2018 ; Qu et al, 2021 ). In a large meta-analysis, it was confirmed that patients with AD had higher plasma t-tau levels than controls, which may reflect neuronal damage as a nonspecific marker (Jack et al, 2018 ; Ding et al, 2021 ). Mattson et al found that the higher plasma t-tau level was associated with AD dementia and showed significant correlations with poor cognition, greater atrophy, and hypometabolism during follow-up in the AD Neuroimaging Initiative study (Mattsson et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, increased CSF t-tau has been found in a variety of other neurological disorders, including frontotemporal dementia [ 4 , 5 , 34 ]. Further, CSF p-tau181 is a highly specific biomarker of AD pathology [ 4 , 5 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased CSF t-tau has been found in a variety of other neurological disorders, including frontotemporal dementia [ 4 , 5 , 34 ]. Further, CSF p-tau181 is a highly specific biomarker of AD pathology [ 4 , 5 , 34 ]. Our results show that there was no difference in the level of CSF tau and p-tau181 (ESM Table 2) at baseline and treatment at week 52.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations